(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Turbine blades are the most important and expensive part of turbines; the losses due to maintenance is very large so must be analyze the causes of failure that may occur due to manufacturing defects or vibrations resulting from operating and other service conditions. In this work will, focus on vibrationthat occurs due to operating conditions. The blade represents as a cantilever beam manufactured fromaluminum, a square crack have constant breadth 5 mm formed on the blade for positions from (5 to 30) cm to fixed end with different crack depths (2,4,6) mm.The experimental work results were computed by using impulse test, and numerical result gain using finite element method. Good agreement was found between the results.The results showed that the increasing in crack’s depth caused decreasing in the fundamental natural frequency of blade for all crack positions.